Laboratory solid waste from practical activity as activated carbon precursor for reducing methylene blue in the laboratory wastewater - Aninda Tifani Puari (Labor Dasar dan Sentral Universitas Andalas, 2020)
Activated carbon (AC) from agricultural waste has become one promising way to produce AC regarding to low price of the precursor and its effect to environment. In this research, the solid waste from the basic biology practical in UPT. Basic and Central Laboratory, Andalas University (Unand) was utilized as the precursor for producing low price AC. The activation was done by chemical activation using three different activating agents which were zink chloride (ZnCl2), phosphoric acid (H3PO4), potassium hydroxide (KOH). The carbonization process was done at temperature of 700°C. The precursor and three different AC after activation were characterized using fourier-transform infrared spectroscopy (FT-IR) to examine the functional group and scanning electron microscope (SEM) to observe the pores structure. The adsorption efficiency (AE) of each AC on methylene blue (MB) contained in laboratory wastewater was examined through adsorption process with retention time of 30 minutes at room temperature and neutral pH. SEM analysis showed that the three activating agents were resulting in higher surface area and more pores were formed. The highest AE of MB from laboratory wastewater for each AC were 97,5 %, 96,31%, and 90,79 for KOH, , ZnCl2, and H3PO4, respectively. Meanwhile, the highest adsorption capacity was achieved by AC through KOH activation with 0,003 mg/g